Value influencing mechanism of green certificates in the discounted cash flow valuation - Vimpari, Jussi; Junnila, Seppo (International Journal of Strategic Property Management, 2014)
The market value of green properties is already acknowledged in scientific literature, but it has still remained unclear how green certificates are incorporated into property valuation. In this study, value influencing mechanism of green certificates in property investment is studied. A widely used discounted cash flow (DCF) model for property valuation was constructed and communicated with spreadsheet to industry professionals for valuing an office property in metropolitan Finland. The goal was to understand the value influencing mechanism and even deeper to identify the differences in DCF parameters between certified properties and non-certified properties. The results show that a green certificate increases on average the property value with 9.0% in the DCF valuation model. Improved yield and net rental income were the main reasons for the higher property value. Interestingly, this is the first known study to empirically open the value influencing mechanisms of green properties presented in earlier theoretical studies. First Publish Online: 18 Sep 2014